Robin Hood in reverse: Persistence and barriers to redistributive fiscal policy - Pedro Cavalcante (Institute for Applied Economic Research (ipea), 2021)
Despite improvements in the living conditions of the population, there has not been a significant change in income disparities. Since the growth of left-wing parties and political competition as per the median voter hypothesis do not stand in the Brazilian case, what could explain the tenacity of inequality in the country? To answer this, the paper, grounded in new institutionalism theory, employed a process-tracing method to explore the causes of the continuity of unequal income distribution in Brazil. The inquiry tests the mechanism using the case of redistributive fiscal policy and the literature of electoral rules and business influence in the political system. This analysis reinforces that the Brazilian government not only misuses its fiscal instruments to distribute income, but also acts as a 'Robin Hood in reverse': that is, it withdraws from those who have less to subsidize or pay transfers to those who have more.
Keywords: H83; 330; Brazil; fiscal policy; inequality; institutions; political economy